The source of teacher work stress: a factor analysis approach - Arismunandar Arismunandar; Nurhikmah H.; Andi Wahed; Hengki Wijaya; Hasnawi Haris (Jurnal Cakrawala Pendidikan, 2022)
This research is motivated by work stress among teachers with various negative impacts on physical, mental, and performance health. The purpose of the study was to determine the level of teacher work stress and its sources in South Sulawesi. The method used is a survey method and a factor analysis approach. The research subjects were teachers in South Sulawesi. The data collection technique used a questionnaire. Then it was analyzed quantitatively descriptively. Quantitative data analysis is the validity and reliability which is declared statistically valid. The results showed that teacher work stress in South Sulawesi was moderate, with a data trend of 41.9%. The category of work stress is based on six sources of work stress, namely (1) welfare; (2) teaching; (3) students; (4) relationships and conflicts; (5) organizational climate; and (6) the time dimension with the dominant or general source of teacher work stress comes from welfare factors and teaching factors, while other teacher work stress factors are student factors and organizational climate. The factor analysis approach shows that the six indicators are combined in only one factor in the work stress source variable.